Upaya Peningkatan Hasil Belajar Speaking Dan Minat Belajar Siswa Kelas X Mekatronika 1 SMKN 6 Pekanbaru Melalui Metode Demonstrasi Pada Mata Pelajaran Bahasa Inggris - Maikhel Rusmana Ibrahim; Khairul Anshari Seirumpun (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
This study aims to determine whether the Demonstration Method can improve Student Speaking Learning Outcomes, determine whether the use of the Demonstration Method can increase Student Learning Interest, find out how learning activities during learning activities using the Demonstration Method. The research method used is the Classroom Action Research method, which is a research conducted in the classroom, where researchers study and reflect collaboratively on a learning approach with the aim of improving the process and results of teaching in the classroom through improvement. The results of the research and discussion concluded that the application of the demonstration method can increase students' interest in learning.